Hasil Analisis SWOT Masalah Transparansi dalam Manajemen Humas yang Ada di Pohuwato - Muh. Wahyuddin S. Adam; Putri Adeliya Masiu; Nurhalifa Nengo; Siti Nurminawati (Jurnal Pendidikan dan Sastra Inggris, 2025)
Public information transparency is a crucial element of good governance principles. Pohuwato Regency, one of the administrative regions in Gorontalo Province, continues to face significant challenges in implementing public information disclosure. The role of the Regional Government's Public Relations (PR) division in disseminating information has not functioned optimally, as indicated by the limited public access to important and strategic governmental information. This study aims to analyze transparency issues in Pohuwato using a SWOT analysis approach (Strengths, Weaknesses, Opportunities, Threats). The research employs a descriptive qualitative method through interviews with PR officials, staff from the Communication and Information Office (Kominfo), and members of the community. The findings indicate that there is internal potential to be developed, such as the commitment of some officials to serve the public. However, weaknesses persist, including inadequate infrastructure and budgetary support. Opportunities to enhance transparency exist through the utilization of digital technology and national policy support, yet these are challenged by low information literacy among the public and a culture of bureaucratic secrecy. In conclusion, public information transparency in Pohuwato requires comprehensive and sustainable reform in public relations management.